Pengaruh Internet Of Things (IoT), Service Quality dan Digital Payment System Terhadap Peningkatan Visitor Experience pada Destinasi Wisata dalam Perspektif Bisnis Islam: Studi pada Pengunjung di Sektor Wisata Lampung, Indonesia - Azizah Karunia Azhari; Mardhiyah Hayati; Diah Mukminatul Hasimi (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
This study was conducted to determine the effect of Internet of Things (IoT), service quality, and digital payment system on the improvement of visitor experience at tourist destinations in Lampung, Indonesia, within the perspective of Islamic business. The independent variables used in this study were IoT, service quality, and digital payment system, while the dependent variable was visitor experience. This study employed a quantitative approach. The sampling technique used was non-probability sampling with a purposive sampling design. The sample consisted of 100 visitors who had experience using digital services at tourist destinations in Lampung. The data analysis method used in this study was SmartPLS. The results of this study indicate that H1, namely IoT has a significant effect on visitor experience, is accepted. H2, namely service quality has a significant effect on visitor experience, is accepted. H3, namely digital payment system has a significant effect on visitor experience, is accepted.